Demand or supply? An empirical exploration of the effects of climate change on the macroeconomy - Matteo Ciccarelli; Fulvia Marotta (European Central Bank (ECB), 2021)
The macroeconomic effects of climate-related events and climate policies depend on the interaction between demand- and supply-type of shocks that those events and policies imply. Using a panel of 24 OECD countries for the sample 1990-2019 and a standard macroeconomic framework, the paper tests the combined effect of (1) climate change, (2) environmental policies and (3) environment-related technologies on the macroeconomy. Results show that climate change and policies to counteract them have a significant, albeit not sizeable, macroeconomic effects over the business cycle. We find evidence that physical risks work as negative demand shocks while transition policies or technology improvements resemble downward supply movements. Furthermore, the disruptive effects on the economy are exacerbated for countries without carbon tax or with a high exposure to natural disasters. Overall our results support the need for a uniform policy mix to counteract climate change with a balance between demand-pull and technology-push policies.
Keywords: C11; C33; E32; E58; Q5; 330; Environmental policy; Environment-related technologies; Physical risks; Business cycle; SVAR